Serum N‐glycome alterations in breast cancer during multimodal treatment and follow‐up. Issue 10 (24th July 2017) - Saldova, Radka; Haakensen, Vilde D.; Rødland, Einar; Walsh, Ian; Stöckmann, Henning; Engebraaten, Olav; Børresen‐Dale, Anne‐Lise; Rudd, Pauline M.
Abstract : Using our recently developed high‐throughput automated platform, N ‐glycans from all serum glycoproteins from patients with breast cancer were analysed at diagnosis, after neoadjuvant chemotherapy, surgery, radiotherapy and up to 3 years after surgery. Surprisingly, alterations in the serum N ‐glycome after chemotherapy were pro‐inflammatory with an increase in glycan structures associated with cancer. Surgery, on the other hand, induced anti‐inflammatory changes in the serum N ‐glycome, towards a noncancerous phenotype. At the time of first follow‐up, glycosylation in patients with affected lymph nodes changed towards a malignant phenotype. C‐reactive protein showed a different pattern, increasing after first line of neoadjuvant chemotherapy, then decreasing throughout treatment until 1 year after surgery. This may reflect a switch from acute to chronic inflammation, where chronic inflammation is reflected in the serum after the acute phase response subsides. In conclusion, we here present the first time‐course serum N ‐glycome profiling of patients with breast cancer during and after treatment. We identify significant glycosylation changes with chemotherapy, surgery and follow‐up, reflecting the host response to therapy and tumour removal. Abstract : Sugars present on proteins in circulating blood of patients with breast cancer change during treatment. Changes in sugars after neoadjuvant chemotherapy and in first follow‐up in patients with affected lymph nodes were towards a malignant phenotype, and after surgery towards a healthy phenotype. C‐reactive protein increased after chemotherapy and decreased until first follow‐up, reflecting a switch from acute to chronic inflammation.